2013
DOI: 10.1017/s0030605312000944
|View full text |Cite
|
Sign up to set email alerts
|

Critical population status of the jaguar Panthera onca in the Argentine Chaco: camera-trap surveys suggest recent collapse and imminent regional extinction

Abstract: The population of jaguars Panthera onca in the semi-arid Chaco Province is the least well-known in Argentina. Its status in the region is described only from interviews that confirmed its presence until 2003. To update information on the distribution and population density of this species we undertook three camera-trap surveys, combined with searches for sign, at sites across latitudinal and protection gradients, and 156 interviews with local inhabitants across three larger areas. The camera-trap sites were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
3
33
0
3
Order By: Relevance
“…The use by jaguars of defined corridors between the Baritú-Calilegua, Chaco and Gran Chaco JCUs has, however, been demonstrated to be extremely limited in the Bolivian Yungas and the Bolivian and Argentine Chaco (Thompson & Martinez 2015). This supports the validity of our approach to cost-limit linkages between JCUs, which is further reinforced by the critically endangered status of the jaguar population in the Argentine Chaco (Altrichter et al 2006, Quiroga et al 2014). Focusing upon the cost-limited linkage network demonstrates how ongoing land use change in eastern Bolivia has resulted in the loss of direct connectivity between the southwest Amazon and Chiquitano forest (Noel Kempff Mercado JCU) and the Bolivian and Paraguayan Chaco (Gran Chaco JCU), in addition to the isolation of the southern and easternmost JCUs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The use by jaguars of defined corridors between the Baritú-Calilegua, Chaco and Gran Chaco JCUs has, however, been demonstrated to be extremely limited in the Bolivian Yungas and the Bolivian and Argentine Chaco (Thompson & Martinez 2015). This supports the validity of our approach to cost-limit linkages between JCUs, which is further reinforced by the critically endangered status of the jaguar population in the Argentine Chaco (Altrichter et al 2006, Quiroga et al 2014). Focusing upon the cost-limited linkage network demonstrates how ongoing land use change in eastern Bolivia has resulted in the loss of direct connectivity between the southwest Amazon and Chiquitano forest (Noel Kempff Mercado JCU) and the Bolivian and Paraguayan Chaco (Gran Chaco JCU), in addition to the isolation of the southern and easternmost JCUs.…”
Section: Discussionsupporting
confidence: 74%
“…Letters correspond to JCUs shown in Fig. 1 De Angelo et al 2011, 2013, Quiroga et al 2014, Thompson & Martinez 2015, Paviolo et al 2016, and consequently is of particular concern for the conservation of the species at the regional scale, and for range-wide efforts for the integrated management of the species. The loss of connectivity among the eastern-and southern-most JCUs in the study area suggested by our modeling is supported for the Atlantic forest, where connectivity of jaguar populations is considered to be greatly compromised due to historic deforestation (Haag et al 2010, Paviolo et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the puestos promote degradation of vegetation diversity and biomass, and habitat quality for vertebrates (Altritcher, Boaglio, & Perovic, 2006;Blanco, Biurrun, & Ferrando, 2005;Grau et al, 2008). This result implies that if food production were maintained at the present level, the puestos (land sharing) can contribute to the conservation of bird populations similarly than under a land-sparing scheme.…”
Section: Discussionmentioning
confidence: 93%
“…Models by and Torres et al (2012) found these areas to be of low suitability for jaguar long-term survival. Recent camera-trap studies and local interviews suggested an imminent regional extinction in the Argentine Chaco (Quiroga et al, 2013), 80% of the people interviewed reported that they had not seen jaguars for many years or that jaguars no longer existed in the region.…”
Section: Population Dynamics Analysismentioning
confidence: 99%